Perspectives on gender in Romania - ILOVAN, Oana-Ramona; SABĂU, Claudia Septimia (2023)
This is the first volume of the Collection Gender and Development, coordinated by dr. Oana‐Ramona Ilovan and dr. Georgeta Fodor.The present volume contributes to a better understanding of gender,gender roles and relations in nowadays Romania and in its recentpast, highlighting women’s position in society, analysing the culturalstereotypes related to them, the political and cultural mechanismsthrough which they had been put apart, the pressures they faced,their daily patterns and behaviours. The interdisciplinary profile of allstudies gathered in the volume is clear and will be focused on step bystep when briefly presenting them. Gender perspectives and insightsare present in the historical, anthropological, anthropo-geographical,legislative approaches the volume contains, as well as in those frommobility studies and visual arts.